Questions and Answers - Saariluoma, Pertti (Human Technology, 2011)
Innovative thinking has become a significant need nowadays. Businesses, governments, and large organizations such as the European Union investigate how innovations could best be fostered. Indeed, policy makers speak often about the importance of innovative thinking. An important social goal of governments involves growing innovative thinking as much as possible in support of their economies. Consequently, one can find abundant literature regarding innovation processes on policy and management level. Yet, we do not have much knowledge or research on innovation as human thinking (Saariluoma, Hautamäki, Väyrynen, Pärttö, & Kannisto, 2011).